Análisis De La Efectividad Del Golpeo en Pádel en Función Del Género, Duración Del Punto Y Tipo De Punto - Iván Martín-Miguel; Bernardino J. Sánchez-Alcaraz; José A. Parraca; Diego Muñoz , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study aims to analyse the winners and errors shot in professional padel according to gender, type of point and the point duration, observing the differences between winners and losers. For this 1927 points of 14 matches (7 male and 7 female category) from the World Padel Tour Master Final 2021 were analyzed, where participated 32 padel players (16 men players and 16 women players), using an ad-hoc instrument obtaining an inter-observer reliability above 0.9. The results show that the effectiveness depending on the gender (p = .001), where the male padel players perform 12% more winners than females padel players. Attending to the importance of the point, winning pairs perform 10% more winner shots than lossers, both in the male category (p=.002) and female (p= .004) in no key points. No differences exist in key points. Point duration affects to the shot effectiveness, specifically in medium duration points in male category (p=.026), and short duration points in female category (p=.007), with a higher winner shot produced by winning pairs. These results have a great practical application for coaches, providing information for the design of training programs similar to competitions situations. In addition, especific strategies can be develop during the matches according to the gender and the score.